Characterization of a novel HLA‐A*33 allele, A*33:47, using next‐generation sequencing. Issue 4 (5th June 2014) - Stückler, C.; Danzer, M.; Raml, E.; Steitzer, H.; Gabriel, C.
<x xml:space="preserve">Abstract</x> HLA‐A*33:47 has a single nucleotide difference to A*33:03:01 at position 181, G > C, in exon 2.